A Prospective Analysis of Complications of Intracranial Tumor Surgery - Sajjad, Jahangir; Kaliaperumal, Chandrasekaran; Yousaf, Irfan; Bhatti, Ramla Javed; O'Sullivan, Michael (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2017)
Aims There is a recent trend toward delivering neurosurgical care in large supraregional centers with intradepartmental subspecialization. We report a 14-year prospective audit of a single surgeon's experience of intracranial tumor surgery with an emphasis on complications.Methods A total of 616 procedures were performed on 596 patients of which 321 were male and 275 were female (age range: 1–84 years). Tumors were categorized as glioma, meningioma, metastasis, and other. Complications were recorded as infection, intracranial hematoma, neurologic deterioration, and death.Results Of the 305 patients who underwent glioma surgery, 4 (1.3%) developed a hematoma, 4 (1.3%) had neurologic deterioration, 5 (1.6%) died within 30 days of surgery, and 1 (0.33%) had an infection. Of the 120 patients who underwent surgery for meningioma, 8 (6.6%) developed an infection, 1 (0.83%) developed a hematoma, and 7 (5.8%) had neurologic deterioration. Of the 59 patients who underwent surgery for brain metastasis, 1 (1.7%) had neurologic deterioration. Of the remaining patients, 4 (3.0%) developed infection and 6 (4.5%) had neurologic deterioration.Conclusions The overall complication rate was infection, 2.1%; hematoma, 0.8%; neurologic deterioration, 2.9%; and death, 0.8%. These results compare favorably with published series.
Keywords: brain tumor; craniotomy; craniotomy complications; centralization